Reproductive traits affect the rescue of valuable and endangered multipurpose tropical trees. (18th August 2015) - Sinébou, Viviane; Quinet, Muriel; Ahohuendo, Bonaventure C.; Jacquemart, Anne-Laure
Abstract : Conservation strategies are urgently needed for widely used tree species. Increasing numbers of species are threatened by overexploitation and their recovery might be poor due to low reproductive success, and poor regeneration rates. One of the first steps for any conservation policy should be an assessment of their reproductive biology. We studied the flowering biology, pollination, breeding system and germination potential of Vitex doniana, a multipurpose threatened African tree. Vitex doniana 's breeding characteristics as well as germination performance offered the required conditions to develop successful conservation strategies. Protection and integration in agroforestry systems could improve the regeneration of the tree. Abstract: Conservation strategies are urgently needed in Tropical areas for widely used tree species. Increasing numbers of species are threatened by overexploitation and their recovery might be poor due to low reproductive success and poor regeneration rates. One of the first steps in developing any conservation policy should be an assessment of the reproductive biology of species that are threatened by overexploitation. This work aimed to study the flowering biology, pollination and breeding system of V. doniana, a multipurpose threatened African tree, as one step in assessing the development of successful conservation strategies. To this end, we studied (1) traits directly involved in pollinator attraction like flowering phenology, flower numbers and morphology, and floral rewards; (2) abundance, diversity and efficiency of flower visitors; (3) breeding system, through controlled hand-pollination experiments involving exclusion of pollinators and pollen from different sources; and (4) optimal conditions for seed germination. The flowering phenology was asynchronous among inflorescences, trees and sites. The flowers produced a large quantity of pollen and nectar with high sugar content. Flowers attracted diverse and abundant visitors, counting both insects and birds, and efficient pollinators included several Hymenoptera species. We detected no spontaneous self-pollination, indicating a total dependence on pollen vectors. Vitex doniana is self-compatible and no inbreeding depression occurred in the first developmental stages. After extraction of the seed from the fruit, seed germination did not require any particular conditions or pre-treatments and the seeds showed high germination rates. These pollination and breeding characteristics as well as germination potential offer the required conditions to develop successful conservation strategies. Protection, cultivation and integration in agroforestry systems are required to improve the regeneration of the tree.